Colorful solar cells utilizing off-axis light diffraction via transparent nanograting structures. (February 2021) - Cho, Dae-Hyung; Hong, Sung-Hoon; Lee, Woo-Jung; Kim, Joo Yeon; Chung, Yong-Duck
Abstract: Various colors are implemented in solar cells without optical losses using light diffractions via grating structure. By utilizing the property of diffraction angle variations depending on the diffraction order, wavelength, grating period, and incident angle, many vivid colors are realized at different observation angles. Well-defined grating structures with periods of 770 nm and 1400 nm are uniformly fabricated on Cu(In, Ga)Se2 thin-film solar cells by a nanotransfer lithography using ZnO nanoparticles. Color-to-angle sensitivity, color brightness, and diffraction efficiency depend on the grating period and incident angle. A wide range of colors, mainly resulting from the 1st-order diffraction are observed in the range of observation angles within 20°. The solar cell performances hardly degrade due to the negligible optical transmission loss in the nanograting structure. The grating applied solar cells show additional advantages: short-circuit current gains in oblique incident light and a self-cleaning effect due to the enhanced hydrophobicity. Through this study, the photovoltaic modules are expected to not only remain as electricity generators, but also become aesthetic structures that can provide aesthetic pleasure to people. Graphical Abstract: ga1 Highlights: Colors were implemented in solar cells using a transparent nanograting structure. A ZnO nanograting was simply imprinted on the Cu(In, Ga)Se2 solar cells. Many distinct colors were realized at various off-axis observation angles. Solar cell performances hardly degraded due to negligible optical loss in the grating. Nanograting enhanced hydrophobicity and optical gain under oblique incident light.